Assessment model of learning responsibility consciousness of student at Ho Chi Minh City University of Technology and Education - Đỗ Thị Mỹ Trang (Journal of Technical Education Science, 2015)
Education of values and skills of living for students are the most important tasks of lecturers. Most importantly, value of responsibility is crucial for all work that student has to obtain. Students must have responsibility for themselves, for works and society. Responsibility is also considered to be condition and constraint for their success. In order to achieve this, students should be taught of responsibility in learning. Things are begun from awareness. Thus, to teach students to form responsibility in learning, lectures need to identify how students realize and practice their task of learning. The purpose of this paper is to introduce an assessment model of learning responsibility consciousness of students in accordance with some theories of awareness assessment model.